Wacana Erotis dalam Sajak Orkestra Pemakaman (2018) Karya Aslan Abidin - Rijal, Andi Samsu; Hukmi, Arif (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
Poetry as a literary work represents the social phenomena of society written by the author. This research aimed to analyze the elements that build erotic discourse in the poetry collection Orkestra Pemakaman (2018) by Aslan Abidin. This research used a qualitative descriptive research method with purposive sampling techniques and flow models. Through Paul Ricouer's hermeneutical approach, this research revealed that the elements of poetry that build erotic discourse include the use of rich diction, strong imagery, diverse figurative language, and deep rhetorical means. Apart from that, the erotic discourse in this anthology also included aspects such as sexuality discourse, power discourse, historical discourse, religious discourse, death euphoria discourse and cultural identity discourse. Erotic discourse was depicted through the meaning of women as objects, the depiction of women's bodies in erotic language, and the reflection of society's views on sexual education. The findings provided an understanding of the relationship between eroticism, religion and cultural identity in the context of South Sulawesi.